Ensemble methods forsolving problems ofmedical diagnosis; Известия Томского политехнического университета [Известия ТПУ]. Промышленная кибернетика; Т. 1, № 1 - Grigoreva A. A. Anastasia Alexandrovna (2023, 2023)
The authors proposed the consolidating method for analyzing series of observations based on a fitted model of a mixture of catalysts of the maincomponents, which makes it possible to study any number of markers. Contrasting the longitudinal approach, it eliminates the need to connect re-gression analysis methods with their own uncertainties when choosing particular models. The consolidating methodallows obtaining an original re-sult in the subject area of early diagnosis of a disease: all options for using markers demonstrate an increase in classification accuracy with an in-crease in the length of a series of examinations